2020
DOI: 10.1002/jccs.202000075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxicity and apoptosis‐inducing activity of novel 1H‐benzo[d]imidazole derivatives of dehydroabietic acid

Abstract: With the expectation of finding new and effective antitumor drugs, a series of novel N-(1H-benzo[d]imidazole-2-yl)-benzamide/benzenesulfonamide derivatives of dehydroabietic acid were synthesized and evaluated for cytotoxic activity against three human cancer cell lines (MCF-7, HeLa, and HepG2 cells) and one human normal hepatocyte cell line (LO2). As a result, a number of derivatives showed moderate to good antitumor activities. Among them, compound 8h exhibited the most potent activities against three cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, compared with that of dehydroabietic acid (IC 50 > 50 µM), it was more toxic to normal cells [87]. Compound 79h was also more cytotoxic against normal human LO2 cell (IC 50 : 42.83 ± 3.18 µM) than dehydroabietic acid (IC 50 > 50 µM) [88]. Based on the above results, when compared with the precursor, the bioactivity of some compounds was significantly improved after structural modifications, but their toxicity against normal human cells was also increased.…”
Section: Structure-activity Relationships Of Dehydroabietic Acid and ...mentioning
confidence: 94%
See 1 more Smart Citation
“…However, compared with that of dehydroabietic acid (IC 50 > 50 µM), it was more toxic to normal cells [87]. Compound 79h was also more cytotoxic against normal human LO2 cell (IC 50 : 42.83 ± 3.18 µM) than dehydroabietic acid (IC 50 > 50 µM) [88]. Based on the above results, when compared with the precursor, the bioactivity of some compounds was significantly improved after structural modifications, but their toxicity against normal human cells was also increased.…”
Section: Structure-activity Relationships Of Dehydroabietic Acid and ...mentioning
confidence: 94%
“…In addition, benzenesulfonamide derivatives (79a−79h) had stronger inhibitory activity than benzamide ones (78a−78h). The most cytotoxic compound 79h (IC 50 : 0.87-9.39 µM) can arrest MCF-7 cells in the S phase through ROS-mediated mitochondrial pathway, and finally induce MCF-7 cell apoptosis [88].…”
Section: Scheme 15 Synthesis Of Compounds 74(a-k)−75(a-k) 77a−77o And...mentioning
confidence: 99%
“…The cytotoxic and apoptosis-inducing activity of benzimidazole derivatives of dehydroabietic acid ( 100 ; see Figure 9 ) were evaluated against MCF-7, HeLa, and HepG2 cancer cell lines and a normal hepatocyte (LO2) cell line by Li et al [ 185 ]. Among these compounds, 216 displayed the highest activity with IC 50 values of 0.87, 9.39, and 8.31 against MCF-7, HeLa, and HepG2 cell lines, respectively.…”
Section: Anticancer Activities Shown By Imidazole Derivatives Through Undefined Mechanismsmentioning
confidence: 99%
“…In addition to inhibiting tubulin polymerization and arresting G2/M phase of the cell cycle, the compound displayed its cytotoxicity against all the cell lines with IC 50 in the range of 0.25 to 1.5 μM [ 61 ]. Using a similar approach, Li et al synthesized a series of imidazole derivatives of dehydroabietic acid and found them to exhibit antitumor activities via cell cycle arrest at the S phase, activation of intracellular ROS and decrease in mitochondrion potential leading to apoptosis [ 62 ]. Among the series, compound 51 exhibited the highest activity against MCF-7 (0.87 μM), HeLa (9.39 μM), and HepG2 cell lines (8.31 μM) [ 62 ].…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%
“…Using a similar approach, Li et al synthesized a series of imidazole derivatives of dehydroabietic acid and found them to exhibit antitumor activities via cell cycle arrest at the S phase, activation of intracellular ROS and decrease in mitochondrion potential leading to apoptosis [ 62 ]. Among the series, compound 51 exhibited the highest activity against MCF-7 (0.87 μM), HeLa (9.39 μM), and HepG2 cell lines (8.31 μM) [ 62 ].…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%